PENGARUH WAKTU AKLIMATISASI YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN UDANG VANAME (Litopeneaus vannamei) - Andre Rachmat Scabra; Iin Satria; Muhammad Marzuki; Bagus Dwi Hari Setyono (Universitas Mataram, 2021)
This study aims to determine the best acclimatization time for survival rate and growth of vaname shrimp. This research was carried out of for 22 days, started from February 5 to 26, 2021 at the Laboratory of Aquaculture Study Program, Faculty of Agriculture, University of Mataram. The research method used a completely randomized design with 5 treatments and 3 replications. Thus in this study there were 15 experimental units. As a treatment is the difference acclimatization periode was the decrease in salinity as follows : Treatment 1 : no decrease in salinity (30 ppt). Treatment 2 : 1 day decreased salinity (30 ppt, 0 ppt). Treatment 3 : 2 day decreased in salinity (30 ppt, 15 ppt, 0 ppt). Treatment 4 : 3 day decreased in salinity (30 ppt, 20 ppt, 10 ppt, 0 ppt). Treatment 5 : 4 day decreased in salinity (30 ppt, 23 ppt, 15 ppt, 8 ppt, 0 ppt). The results showed that the vaname shrimp that were kept at low salinity using acclimatization method had noticeable effect on survival rate. The value of survival rate between 1 % - 73 %, has an absolute weight between 0.0433 gram – 0.1802 gram and an absolute length bewtween 1.1 cm – 2.9 cm with food conversion ratio 0.1285 – 3.937. The oxygen consumption rate between 0.073 – 0.113.